Psychological trauma increases blood pressure sensitivity to angiotensin II via T-lymphocytes independent of psychopathology - Case, Adam J.; Natour, Tamara; Pitts, Lauren J.; Lauten, Tatlock H.; Reed, Emily C.; Moshfegh, Cassandra M.; Elkhatib, Safwan K. (Frontiers in Cellular Neuroscience, 2025)
Exposure to traumatic stress can lead to psychopathology, including post-traumatic stress disorder (PTSD), but may also cause inflammation and cardiovascular dysfunction. Clinical evidence suggests that exposure to traumatic stress, independent of psychopathology development, may be sufficient to induce pathophysiological sequelae, but this has not been thoroughly investigated. Using a novel model of repeated social defeat stress (RSDS) that allows for both sexes, we explored links between the behavioral and physiological consequences of this paradigm. RSDS was sufficiently able to elevate systemic inflammation in both male and female mice, with no observed sex differences. RSDS also induced a heightened blood pressure sensitization response to low dose exogenous angiotensin II (AngII), suggesting the model was also sufficient in generating cardiovascular pathology. Interestingly, the RSDS-induced sensitization to AngII was completely abrogated in mice lacking T-lymphocytes (i.e., Rag2−/− mice). Of note, Rag2−/− mice demonstrated similar pro-social and anxiety-like behavior to wild-type mice, inferring that (1) differences in these behavioral outcomes do not explain the loss of RSDS-induced AngII sensitization in Rag2−/− mice and (2) T-lymphocytes do not appear to impact these specific RSDS-induced behaviors. Indeed, intra-animal correlations demonstrate a tight association between the inflammatory and cardiovascular consequences post-RSDS, but no associations between these parameters with behavior. Together, our data suggest that exposure to traumatic stress, independent of psychopathology, is sufficient to induce pathophysiology. These findings have significant clinical implications, specifically for individuals who have experienced traumatic stress without the development of psychopathology, as this overlooked population may have similar risks of developing somatic diseases.